2012
DOI: 10.1002/bies.201200087
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells for systemic therapy: Shotgun approach or magic bullets?

Abstract: Given their heterogeneity and lack of defining markers, it is surprising that multipotent mesenchymal stem/stromal cells (MSCs) have attracted so much translational attention, especially as increasing evidence points to their predominant effect being not by donor differentiation but via paracrine mediators and exosomes. Achieving long-term MSC donor chimerism for treatment of chronic disease remains a challenge, requiring enhanced MSC homing/engraftment properties and manipulation of niches to direct MSC behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 114 publications
1
18
0
Order By: Relevance
“…There is some concern that exogenously delivered MSCs have an unpredictable effect on tumour biology with different in vivo models suggesting pro-tumourigenic or antitumourigenic properties,27 but MSCs genetically modified to express pro-apoptotic molecules ensure an antitumourigenic effect 28. This is in line with our results where MSCs alone had no pro-tumourigenic effect and intravenous MSCTRAIL had an antitumourigenic effect.…”
Section: Discussionsupporting
confidence: 89%
“…There is some concern that exogenously delivered MSCs have an unpredictable effect on tumour biology with different in vivo models suggesting pro-tumourigenic or antitumourigenic properties,27 but MSCs genetically modified to express pro-apoptotic molecules ensure an antitumourigenic effect 28. This is in line with our results where MSCs alone had no pro-tumourigenic effect and intravenous MSCTRAIL had an antitumourigenic effect.…”
Section: Discussionsupporting
confidence: 89%
“…If MSCs are rejected after they express class II MHC markers, it does not preclude the use of allogeneic MSCs in cases where MSCs are not expected to differentiate. In fact, many studies have shown that allogeneic MSCs are well tolerated in people, and many of the positive results observed in various clinical trials have come from patients transplanted with allogeneic MSCs (reviewed by Millard and Fisk [12]). However, it may be that, in many studies, the observed therapeutic effects do not require long-term engraftment.…”
Section: Msc Immune Modulationmentioning
confidence: 99%
“…In addition to direct differentiation into end-stage phenotypes, MSCs have also been shown to have a positive therapeutic effect in many repair situations because of their capacity to secrete trophic factors (reviewed in [6]) that contribute to repair via the promotion of vascularization and the inhibition of cell death as well as through the modulation of the immune response. Currently, there are over 160 open studies and 116 closed clinical trials (results retrieved (3rd June 2013) in a search of www.clinicaltrials.gov on the search term “mesenchymal stem cells” and excluding trials with an unknown status and those that were conducted in vitro ) that use MSCs to treat a variety of conditions that range from direct formation of bone tissue to treatments for graft versus host disease (GvHD) [79], myocardial infarction, brain trauma, and multiple sclerosis [10, 11] (reviewed by Millard and Fisk [12]). Indeed, MSCs have been well characterized with respect to their ability to produce a range of growth factors and cytokines, which inspired the designation of these cells as a kind of “injury drugstore” [13].…”
Section: Introductionmentioning
confidence: 99%
“…Because of their immunomodulatory properties, increasing experimental and early clinical observations indicate that allogeneic, and even xenogeneic, MSCs may be useful for tissue transplantation [108]. Despite their heterogeneity and lack of defining markers, the MSCs have attracted so much translational attention as increasing evidence points to their predominant effect being not by donor differentiation but via paracrine mediators and exosomes [109]. Also, the immune tolerance with MSCs is well investigated in various animal studies.…”
Section: Future Perspectivesmentioning
confidence: 99%